Seasonal Hydro-Climatic Consequences on Fish Harvests in the Vavuniya Reservoir, Sri Lanka - Patrick, A.E.S.; Kuganathan, S. (University of Jaffna, 2016)
Vavuniya reservoir is a tropical lowland shallow irrigation tank located in Vavuniya District, Northern Province, Sri Lanka.As it is situated in the dry zone, experiencing the water scarcity probably due to the climate related changes which in turn affect the seasonal hydro-climatic factors recently. This study focused on the effects of seasonal hydro harvests in this reservoir. The major hydro-climatic factors are monthly total rainfall (RF) and monthly mean water level (WL). RF, WL, catch/harvest and effort data were collected from January 2013 to December 2014. Semester and quarter wise categorization of both years were done based on RF and WL by using moving average techniques. There was no correlation between RF and WL (p= 0. 606 & r = 0.231) due to irrigation.In 2013, the annual fish harvest was 16 130 kg and in 2014 it was 27 005 kg. The WL showed a strong negative correlation and a significant (p=0.037) relationship between most catchability variables compared with RF. Direct and the indirect effect of climate related changes influenced the seasonal pattern of this hydro-climatic factors which in turn affect the fish harvest and fish species survival in this reservoir. Findings of this study reflected the current changes in seasonality and its consequent threats to fisheries. Hence, optimal fish harvests can be achieved via rational understanding of this baseline information in Vavuniya reservoir.
Keywords: Seasonality; Hydro-climatic factors; Fish harvest